Gambaran Perilaku Hidup Bersih dan Sehat (PHBS) di RW.4 Kelurahan Tallo Kecamatan Tallo Kota Makassar: Description of Clean and Healthy Lifestyle Behavior (PHBS) in the Family in RW.4 Tallo Kelurahan Tallo District, Makassar City - Inda Pusvitasari; Nur Fajri Hartanto; Hardi; Mutmainnah Latief; Asmarani Harma; Nur Alsabfitri Usmani (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2023)
Introduction Based on the results of observations, researchers conducted research in RW.4 Tallo Subdistrict, Makassar City on the grounds that there are still many people who do not know the importance of Clean and Healthy Behavior (PHBS) in the family and have not fully implemented it, seeing the conditions there are slum areas and people who are pre-prosperous. Method descriptive research with mapping of PHBS areas based on 5 indicators in the family in RW.4 Tallo Village, Makassar City. The population in this study was 370 households and no sampling was carried out. Result The research shows that 98.6% of households (RT) giving birth by health personnel are midwives, 84.1% give exclusive breastfeeding, 92.2% weigh babies and toddlers, 95.1% use clean water, washing hands using clean water and soap is 91.1%. Conclusion Based on the research results, the majority of clean and healthy living behaviors (PHBS) in families have not met the target of households with PHBS applied, namely 75%. The community as the target of this program should have full awareness to apply Clean and Healthy Behavior (PHBS) as one of the indicators for creating a healthy city.